Mutations and clinical significance of calcium voltage-gated channel subunit alpha 1E (CACNA1E) in non-small cell lung cancer. (March 2022) - Gao, San-Hui; Wang, Gui-Zhen; Wang, Li-Peng; Feng, Lin; Zhou, Yong-Chun; Yu, Xian-Jun; Liang, Fan; Yang, Fu-Ying; Wang, Zheng; Sun, Bei-Bei; Wang, Di; Liang, Li-Jun; et al.
Highlights: CACNA1E is frequently mutated in non-small cell lung cancers of both Chinese and Caucasian patients. CACNA1E is overexpressed in non-small cell lung cancers. CACNA1E as well as its mutants is functional as a calcium channel. CACNA1E is able to regulate EGFR phosphorylation. CACNA1E is required lung cancer cell proliferation in vitro and in vivo . Abstract: CACNA1E is a gene encoding the ion-conducting α1 subunit of R-type voltage-dependent calcium channels, whose roles in tumorigenesis remain to be determined. We previously showed that CACNA1E was significantly mutated in patients with non-small cell lung cancer (NSCLC) who were long-term exposed to household air pollution, with a mutation rate of 19% (15 of 79 cases). Here we showed that CACNA1E was also mutated in 207 (12.8%) of the 1616 patients with NSCLC in The Cancer Genome Atlas (TCGA) datasets. At mRNA and protein levels, CACNA1E was elevated in tumor tissues compared to counterpart non-tumoral lung tissues in NSCLCs of the public datasets and our settings, and its expression level was inversely associated with clinical outcome of the patients. Overexpression of wild type (WT) or A275S or R249G mutant CACNA1E transcripts promoted NSCLC cell proliferation with activation of epidermal growth factor receptor (EGFR) signaling pathway, whereas knockdown of this gene exerted inhibitory effects on NSCLC cells in vitro and in vivo . CACNA1E increased current density and Ca 2+ entrance, whereas calcium channel blockers inhibited NSCLC cell proliferation. These data indicate that CACNA1E is required for NSCLC cell proliferation, and blockade of this oncoprotein may have therapeutic potentials for this deadly disease. Graphical Abstract: Image, graphical abstract .